EVALUATION OF THE ARCHITECTURAL AND STRUCTURAL RELIABILITY OF BUILDINGS IN PALANGKA RAYA CITY: Case Study: Tjilik Riwut Multiuse Building, Palangka Raya - Giris Ngini; Fransisco Happy Riadi Haputra Baru; Evan Kurniawan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
Based on Law Number 28 of 2002 concerning building construction in article 3 states that to realize a functional building and in accordance with the building layout that is harmonious and in harmony with its environment, it must guarantee the building in terms of safety, health, comfort and convenience. There are two important aspects in the assessment process that highlight the building, namely; architectural and structural aspects of the building. Architectural assessment is an evaluation of the physical and functional condition of the building, including components such as walls, doors, windows, floors, ceilings, as well as circulation and spatial layout, with the aim of ensuring the building functions well, safely, and comfortably for users. Structural reliability assessment refers to the ability of a building structure to maintain its integrity and stability during its expected service life. Several factors that influence structural performance include the selection of appropriate materials, good design, the use of correct construction techniques, and routine maintenance. As a Case Study of the Research is the Tjilik Riwut Multipurpose Building in Palangka Raya City. The output target of this research is the publication of articles in SINTA and HKI accredited journals.